2016
DOI: 10.1007/s00432-016-2273-6
|View full text |Cite
|
Sign up to set email alerts
|

Gli1, a potential regulator of esophageal cancer stem cell, is identified as an independent adverse prognostic factor in esophageal squamous cell carcinoma

Abstract: Targeting Gli1, a potential diagnostic marker of ESCC stem cells, will have a profound therapeutic and prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…They further showed that GLI-1 expression correlated directly with important cancer stem cell markers, including SOX9 and CD44 that are involved in epithelial-tomesenchymal transition (EMT). 16,17 Interestingly, Yang and colleagues found a positive GLI-1 expression in 28.3% of all cases, which correlated with the expression pattern of SMO (35.6%). In our cohort we have also demonstrated a direct correlation between SMO and GLI-1 expression, but in contrast to Yang, GLI-1 expression was no significant indicator of worse overall or disease-free survival.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…They further showed that GLI-1 expression correlated directly with important cancer stem cell markers, including SOX9 and CD44 that are involved in epithelial-tomesenchymal transition (EMT). 16,17 Interestingly, Yang and colleagues found a positive GLI-1 expression in 28.3% of all cases, which correlated with the expression pattern of SMO (35.6%). In our cohort we have also demonstrated a direct correlation between SMO and GLI-1 expression, but in contrast to Yang, GLI-1 expression was no significant indicator of worse overall or disease-free survival.…”
Section: Discussionmentioning
confidence: 92%
“…demonstrated that high GLI‐1 expression was associated with inferior outcome. They further showed that GLI‐1 expression correlated directly with important cancer stem cell markers, including SOX9 and CD44 that are involved in epithelial‐to‐mesenchymal transition (EMT) . Interestingly, Yang and colleagues found a positive GLI‐1 expression in 28.3% of all cases, which correlated with the expression pattern of SMO (35.6%).…”
Section: Discussionmentioning
confidence: 96%
“…IHC staining and evaluation of the IHC analysis on CRC tissue microarray samples was performed as previously described [8]. The primary antibody include anti-TNC (1:100, Abcam, UK), anti-SOX2 (1:100, Abcam, UK), anti-CD44 (1:80, Millipore, USA), anti-CD133 (1:100, NOVUS, USA), anti-LSD1 (1:250, Sigma, USA), anti-SOX9 (1:100, Abnova, USA), anti-p21 (1:100, Millipore, USA), anti-cyclinD1 (1:100, Millipore, USA), anti-p27 (1:100, Millipore, USA), anti-CDK4 (1:100, Millipore, USA), anti-p16 (1:100, Millipore, USA), anti-SMO (1:250, Santa, USA), and anti-GLI1 (1:100, Abcam, UK).…”
Section: Immunohistochemical (Ihc) Staining Proceduresmentioning
confidence: 99%
“…Western blot analysis were carried out according to the standard procedures [8] for anti-TNC (1:1000, Abcam, UK), anti-LSD1 (1:2000, Sigma, USA), anti-SOX2 (1:1000, Abcam, UK), anti-CD44 (1:1000, Millipore, USA), anti-CD133 (1:1000, NOVUS, USA), anti-SOX9 (1:1000, Abnova, USA), anti-GLI1 (1:1000, Abcam, UK), and anti-β-actin (1:500, Bioss, China).…”
Section: Western Blotting Analysismentioning
confidence: 99%
“…Others have evaluated the predictive role of ubiquitin‐specific protease 22 (USP22) and found USP22 overexpression in approximately 50% of ESCC patients, which was associated with poorer 5‐year survival rates . Glioma‐associated oncogene homolog 1 (Gli1), CD44, and SOX9 expression have been linked to worse clinical outcome and poor prognosis of overall survival ( P = 0.005) and disease‐free survival ( P = 0.003) in ESCC . Testing of 328 ESCC and adjacent normal tissues showed that TRAP1‐positive patients had higher mortality and shorter overall survival, indicating that TRAP1 might be a protein predictive marker for poor prognosis, High ZBP‐89 expression in ESCC patients was correlated with shorter overall survival, compared with low ZBP‐89 expression level, and high expression of BRF2 protein was closely associated with tumor progression, angiogenesis, and poor survival of ESCC patients .…”
Section: Potential Protein Biomarkers For the Prognosis Of Esccmentioning
confidence: 99%